HIV-1 Subtypes and treatment outcome among adults on Antiretroviral therapy at tertiary hospital in Moshi, Tanzania (Tanzania Medical Journal, 2017)
Background: Human Immunodeficiency virus (HIV) is characterized by great genetic diversity due to its high mutations that occur during replication. Its infection also characterized by high rates of viral turnover and extensive viral diversity. This diverse has implication on disease progression, diagnostic strategies, vaccine development as well as treatment response to antiretroviral drugs.Methods:  63 HIV positive adults infected by different HIV-1 Subtypes at Kilimanjaro Christian Medical Centre (KCMC) in Moshi, Tanzania were studied. HIV-1 Subtypes were characterized using peptide ELISA representing HIV-1 subtypes A, B, C, D and E derived from consensus gp 120 V3 sequences. The CD4+T-lymphocyte cell counts were measured at baseline, six and twelve months using FACS Calliber (Becton Dickinson, San Jose, CA, USA).Results: HIV-1 Subtype A was the most prevalent (47.62%), followed by Subtype C (36.51%) and Subtype D (15.87%). Subtype D showed higher immunological and clinical failures as compared to subtype A and C with Hazard Ratio (H.R, 5.6) and 95% CI=1.3-5.2, P=0.02). After adjustment for sex, baseline CD4+ T Lymphocyte and clinical stage, the association remained the same.Conclusions: HIV-1 A was the most predominant followed by C and D was less predominant. HIV-1 D showed rapid progression of diseases with poor treatment outcomes relative to others subtypes.